Цивільне населення радянської України в полі зору військових трибуналів: реґламентація каральних практик (1918–1959 рр.) - Вронська, Т.; Пилипчук, В.; Беланюк, М. (Український історичний журнал, 2021)
Метою статті є встановлення причин і процедури зміни підсудності стосовно
пересічних громадян, обвинувачених у вчиненні злочинів, які впродовж досліджуваного періоду
йменувалися «контрреволюційними», «державними» або «політичними». Аналізується процес
перетворення військових трибуналів на невід’ємну складову інструментарію політичного терору.
Зумовлені метою дослідницькі завдання полягають у виявленні особливостей розширення
юрисдикції військових трибуналів періоду 1918–1959 рр. та їх каральних практик у мирний час,
коли ці інституції, відповідно до класичних норм права, мали б займатися лише військовими
правопорушеннями, але фактично перетворилися на знаряддя політичної розправи з тими, кого
влада вважала «особливо небезпечними злочинцями». Методологія дослідження поєднує
інструментарій історичного та історико-правового аналізу. Наукова новизна полягає в
розширенні уявлення про інструментарій політичного терору. Завдяки новим документам також
можна простежити дрейф радянського судочинства в бік перманентної «надзвичайщини» задля
спрощення процедури розправи, а також зазирнути за лаштунки суперечностей між різними
інституціями військової юстиції в боротьбі за застосування найжорстокіших покарань. Висновки.
Доведено, що з ініціативи компартійної верхівки, іґноруючи засадничі норми кримінально-
процесуального законодавства, військові трибунали з часу встановлення радянської влади на
теренах України наділялися надширокими повноваженнями у сфері судочинства стосовно
цивільних осіб, обвинувачених в «антидержавних» злочинах. Поряд із позасудовими органами
(«трійками», революційними трибуналами, особливими нарадами при НК, ОДПУ, НКВС,
МВС, МДБ тощо) військові трибунали в розглянутий історичний період стали органічною
складовою радянської юридичної системи та інструментарієм протиправного свавілля. The article analyzes and highlights the process of transforming military tribunals into
an integral part of the tools of political terror. The focus is on expanding the powers of these
institutions by referring civilians to their jurisdiction not only in wartime or emergencies, but also
in peaceful years, when military justice, in combination with extrajudicial bodies that administer
“justice” in a simplified manner, became a means of combating real and imaginary opponents of
Soviet power. In this way, a common tradition of the totalitarian regime was revealed, when the
neglect of human rights was the norm, not the exception. The purpose of the article is to establish
the reasons and procedure for changing the jurisdiction of ordinary citizens accused of committing
“crimes”, which during the period under study were called “counter-revolutionary”, “state” or
“political”. The research objectives are to identify the features of expanding the jurisdiction of
military tribunals in the period 1918–1959 and their penal practices in “peaceful” times, when
these institutions, according to classical law, should “take care” only of military offenses, but in fact
became instruments for political massacre of those whom the authorities considered “especially
dangerous criminals.” Research methodology combines the tools of historical and legal analysis,
which makes it possible to understand the historical features of the formation of the mechanisms
of the Soviet legal system and highlight the institutionalization of total human rights violations that
were characteristic for the Soviet repressive system. Scientific novelty, first of all, is to expand the
idea of the tools of political terror. Thanks to the new documents, it is also possible to trace the
drift of the Soviet judiciary towards permanent “emergency” in order to simplify the procedure
of execution, as well as to look behind the scenes of contradictions between different institutions
of the military Themis in the struggle for the most severe punishments. Conclusions. It has been
proven that, at the initiative of the Bolshevik and Communist Party leaderships, ignoring the basic
norms of criminal procedure law, military tribunals have been given excessive powers in the field
of justice against civilians accused of “anti-state” crimes since the establishment of Soviet power in
Ukraine. Along with extrajudicial bodies (troikas, revolutionary tribunals, special meetings at the
Cheka / Extraordinary Commission, OGPU / Joint State Political Directorate, NKVD / People’s
Commissariat for Internal Affairs, MIA, MGB / Ministry for State Security, etc.) military tribunals
became an organic component of the Soviet Themis and an instrument of illegal arbitrariness in the
Soviet state.